Virtually united: The role of the internet in building social capital - Cardozo, Ginna Tovar (AWARI, 2023)
This article examines the transformation of social capital in the context of the digital era, highlighting the significant role of the Internet in this process. Three main areas of impact are identified: the increase in online community participation, enabling people to overcome geographic and temporal barriers to engage in civic and cultural activities; the strengthening of personal social networks through digital platforms, crucial during periods of physical isolation; and the diversification of social capital, facilitating the inclusion of marginalized groups and access to a wider range of support networks. This study highlights how the Internet has served not only as a tool to maintain and expand interpersonal relationships, but also as a means to promote equity, social inclusion and collective mobilization. However, it emphasizes the need to address challenges such as the digital divide and online privacy concerns in order to maximize the positive potential of the Internet. It is concluded that the Internet represents an invaluable resource for building a more robust and diversified social capital in the 21st century.